Viperin is an iron‐sulfur protein that inhibits genome synthesis of tick‐borne encephalitis virus via radical SAM domain activity. (3rd December 2013) - Upadhyay, Arunkumar S.; Vonderstein, Kirstin; Pichlmair, Andreas; Stehling, Oliver; Bennett, Keiryn L.; Dobler, Gerhard; Guo, Ju‐Tao; Superti‐Furga, Giulio; Lill, Roland; Överby, Anna K.; Weber, Friedemann
Summary Viperin is an interferon‐induced protein with a broad antiviral activity. This evolutionary conserved protein contains a radical S‐adenosyl‐l‐methionine (SAM) domain which has been shown in vitro to hold a [4Fe‐4S] cluster. We identified tick‐borne encephalitis virus (TBEV) as a novel target for which human viperin inhibits productionof the viral genome RNA. Wt viperin was found to require ER localization for full antiviral activity and to interact with the cytosolic Fe/S protein assembly factor CIAO1. Radiolabelling in vivo revealed incorporation of 55Fe, indicative for the presence of an Fe‐S cluster. Mutation of the cysteine residues ligating the Fe‐S cluster in the central radical SAM domain entirely abolished both antiviral activity and incorporation of 55Fe. Mutants lacking the extreme C‐terminal W361 did not interact with CIAO1, were not matured, and were antivirally inactive. Moreover, intracellular removal of SAM by ectopic expression of the bacteriophage T3 SAMase abolished antiviral activity. Collectively, our data suggest that viperin requires CIAO1 for [4Fe‐4S] cluster assembly, and acts through an enzymatic, Fe‐S cluster‐ and SAM‐dependent mechanism to inhibit viral RNA synthesis.